2019
DOI: 10.1027/2151-2604/a000354
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Interparental Relationships in Families of Children With Attention-Deficit/Hyperactivity Disorder (ADHD)

Abstract: Abstract. Research on attention-deficit/hyperactivity disorder (ADHD) in children and adolescents has traditionally focused on the genetic and neurobiological aspects of the disorder, but the role of family relationships has been much less systematically examined. There is growing evidence that the quality of interparental relationships and a child’s ADHD symptoms are reciprocally related. Because the literature appears to be inconsistent, this meta-analysis aims to summarize previous research and assess wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 67 publications
2
25
1
Order By: Relevance
“…When one of the children has attention deficit disorder, parents experience more stress and have more conflicts with their children, compared to parents with children without ADHD. In addition, the parents' relationships are influenced by the child behavior (Weyers et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…When one of the children has attention deficit disorder, parents experience more stress and have more conflicts with their children, compared to parents with children without ADHD. In addition, the parents' relationships are influenced by the child behavior (Weyers et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to previous studies, only considering the types of inattention can completely alleviate this relationship by externalizing behavior problems. It is better to analyze it in the longitudinal study, but it lacks the content of numerical analysis [ 3 ]. Franke s said the study assessed possible correlations between behavioral profiles, quality of life and perceptions of social support, and parenting styles adopted by 26 mothers of children and adolescents with ADHD diagnosed by the same neurologist.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer studies have examined the opposite direction of influence, in which children's behavioral problems increase parent-child conflicts and stress, which spills over into the marital relationship, creating negativity and marital dissatisfaction. The few studies that did focus on this direction found spillover effects among children diagnosed with behavioral disorders (Ben-Naim et al, 2019;Lin et al, 2017;Weyers et al, 2019), autism spectrum disorder (Sim et al, 2017), and developmental delays (Robinson & Neece, 2015). Our results add to the existing literature in two respects: First, by supporting the existence of a spillover process from the parent-child subsystem to the marital subsystem, which is a less researched direction of influence, and second, by focusing on a population that is not commonly studied and demonstrating this effect among non-referred, typically developing preschool children who exhibit mild behavioral problems at a nonclinical level.…”
Section: Discussionmentioning
confidence: 99%
“…Second, considerable research regarding the association between children's behavioral problems and marital satisfaction has focused on parents of children diagnosed with behavioral disorders, developmental delays, or autism spectrum disorder (e.g., Robinson & Neece, 2015;Sim et al, 2017;Weyers et al, 2019). In the present study, we sought to add to the existing body of knowledge by focusing on a non-clinical sample of typically developing children, and examining the association between their mild behavioral problems and parents' marital satisfaction.…”
Section: Introductionmentioning
confidence: 99%